INFORMATION SOCIETY: FORMATION, DEVELOPMENT, PROSPECTS - Kriukov O.I.; Bielska T.V. (Pressing Problems of Public Administration, 2015)
The paper examines three periods of the information society: interpersonal, media, virtual communications and prospects for the fourth information revolution; the features, positive and negative trends of each period of the information society are analyzed.